Breastfeeding, first-food systems and corporate power: a case study on the market and political practices of the transnational baby food industry in Brazil - Cindy Alejandra Pachón Robles; Mélissa Mialon; Laís Amaral Mais; Daniela Neri; Kimielle Cristina Silva; Phillip Baker (BMC, 2024)
Abstract Background The exploitative marketing of commercial milk formula (CMF) reduces breastfeeding, and harms child and maternal health globally. Yet forty years after the International Code of Marketing of Breast-Milk Substitutes (The Code) was adopted by WHO member states, many countries are still to fully implement its provisions into national law. Furthermore, despite The Code, worldwide CMF markets have markedly expanded. In this paper, we adopt Brazil as a case study to understand the power of the baby food industry's marketing and corporate political activity, and how this influences the country's 'first-food system' in ways that promote and sustain CMF consumption. Methods We used a case study design, drawing data from from documents and key informant interviews (N = 10). Results Breastfeeding rates plummeted in Brazil to a historic low in the 1970s. A resurgence in breastfeeding from the mid-1980s onwards reflected strengthening political commitment for a national policy framework and breastfeeding protection law, resulting in-turn, from collective actions by breastfeeding coalitions, advocates, and mothers. Yet more recently, improvements in breastfeeding have plateaued in Brazil, while the industry grew CMF sales in Brazil by 750% between 2006 and 20. As regulations tightened, the industry has more aggressively promoted CMF for older infants and young children, as well as specialised formulas. The baby food industry is empowered through association with powerful industry groups, and employs lobbyists with good access to policymakers. The industry has captured the pediatric profession in Brazil through its long-standing association with the Brazilian Society of Pediatrics. Conclusion Brazil illustrates how the baby food industry uses marketing and political activity to promote and sustain CMF markets, to the detriment of breastfeeding. Our results demonstrate that this industry requires much greater scrutiny by regulators.